2017
DOI: 10.1515/mcwf-2017-0002
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Transport due to Baroclinic Waves: Linear Analysis of Precipitating Quasi-Geostrophic Dynamics

Abstract: Abstract:The e ects of rainfall speed, V T , and meridional/vertical moisture gradients on the meridional moisture transport are examined in the context of mid-latitude baroclinic waves. These e ects are investigated in an idealized model that can be solved analytically. The model is systematically derived in a precipitating quasi-geostrophic limit, starting from a moist atmospheric model with minimal representation of cloud microphysics. Single-phase dynamics are considered, with a comparison of three cases: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…Gross PV is nearly identical to the ''moist'' PV discussed by Lapeyre and Held (2004). Additionally, as noted by AM18, the gross PV equation bears resemblance to the precipitating QG equations discussed by Smith and Stechmann (2017), and some of the results discussed here resemble studies that use these equations (Wetzel et al 2017(Wetzel et al , 2020. The gross PV equation also bears resemblance to the ''equivalent'' Ertel PV employed by some studies (Rotunno and Klemp 1985;Martin et al 1992;Cao and Cho 1995;Marquet 2014).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Gross PV is nearly identical to the ''moist'' PV discussed by Lapeyre and Held (2004). Additionally, as noted by AM18, the gross PV equation bears resemblance to the precipitating QG equations discussed by Smith and Stechmann (2017), and some of the results discussed here resemble studies that use these equations (Wetzel et al 2017(Wetzel et al , 2020. The gross PV equation also bears resemblance to the ''equivalent'' Ertel PV employed by some studies (Rotunno and Klemp 1985;Martin et al 1992;Cao and Cho 1995;Marquet 2014).…”
Section: Discussionsupporting
confidence: 71%
“…Relative to dry baroclinic instability alone, growth between m 5 0 and m 5 1 exhibits a larger amplitude due to the contribution from moist processes. This larger amplitude was noted in the diabatic Rossby waves examined by de Vries et al (2010), and by the balanced moist waves examined by Wetzel et al (2017). In the case of b 5 0 and b q 5 0 we find that baroclinic instability occurs when k , k d m 21/2 .…”
Section: Solutions For T C =supporting
confidence: 50%
“…Numerous studies involving the evaluation of the right-hand side of Equation (4) with observations datasets and CGCM-simulated data (Coupled atmosphere-ocean general circulation model) have shown that transient eddies dominate meridional moisture transport at mid-latitudes:~80% between 30 • and 40 • north and south latitudes (e.g., [20,40,41,68,[73][74][75][76][77]). One can easily show that for the plane wave solutions (A15), the TE meridional moisture flux is exponentially dependent on the growth rate χ k = kc i of unstable modes [78]. Let L w be the wavelength of a baroclinic unstable wave and k = 2π/L w its wavenumber.…”
Section: Moisture Content and Transport In The Global Atmospherementioning
confidence: 99%
“…While much is known about dry dynamics without moisture (for either balanced or unbalanced initial conditions), much less is known about moist dynamics with phase changes. In the case of balanced initial conditions, with moisture, a formal asymptotic derivation of precipitating QG (PQG) equations has been presented (Smith & Stechmann 2017), and some properties of the PQG equations have been investigated (Wetzel, Smith & Stechmann 2017, 2019 a ; Edwards, Smith & Stechmann 2020 a , b ), but no rigorous proofs have been shown. Unbalanced initial conditions, on the other hand, are the topic of the present paper.…”
Section: Introductionmentioning
confidence: 99%